A265 LYMPHOCYTIC ESOPHAGITIS: A SINGLE TERTIARY CENTER'S EXPERIENCE WITH THIS EMERGING CLINICAL ENTITY. (15th March 2019) - Shams, C; Co, M; Cappell, M
Abstract: Background: Various disorders can produce esophagitis. Lymphocytic esophagitis (LE) has emerged as another clinical entity responsible for esophagitis symptoms. Although increasingly reported pathologically, the clinical characteristics of LE have not been well characterized. Aims: The present study extends the clinicopathologic characterization of LE by comprehensive analysis of 30 affected patients and identifies specific clinical presentations significantly associated with LE. Methods: Thirty patients were identified from January 2000-December 2016 that satisfied diagnostic criteria for LE by lower esophageal biopsy; (1) high concentration of intraepithelial lymphocytes and (2) few granulocytes (ratio of lymphocytes:granulocytes >50:1). Controls, selected from patients undergoing esophagogastroduodenoscopy (EGD) during the same time interval were divided into two groups; control I (N=30) included patients matched for age and sex, and control-II patients (N=30) who were matched for age, sex, and endoscopic indication. Baseline characteristics of the 30 patients with LE were contrasted with the two control groups. Results: Patients with LE were predominantly female and Caucasian. Average BMI was 25.7 ± 5.7. 63% had reflux similar to control I and II patients (57% and 50% respectively; p =>0.05). 17% of the study group had a diagnosis of Crohn's disease versus only 7% in control I and 3% in control II, but these differences were not statistically significant. In the study group, 20% had autoimmune disease versus 7% in each of the control groups ( p =<0.05). Surgical history including esophageal, gastric or colonic surgery was not statistically different, but there was a higher incidence of gastric and colonic surgeries in the study group with 17% versus 3% in control I and 7% in control II. Proton-pump inhibitor (PPI) use was prevalent among all three cohorts with no significant difference between the three groups. Half of the study patients experienced dysphagia. This incidence was significantly greater than that for control I ( p = 0.03) or control II ( p = 0.04). Study patients had esophageal endoscopic findings of esophageal rings (27%), irregular z line (30%), and reflux esophagitis (27%), and these rates were significantly more than those of the controls. The majority of the gastric endoscopic findings showed erythematous nonbleeding gastropathy (53%, p=0.8). Lymphocyte counts in the study group averaged 80.9 ± 59.2/hpf, while that of control group I was 24.2 ± 22.9/hpf and that of control group II was 26.7 ± 26.4/hpf. Eosinophils were rarely detected (eosinophil count=0.4 ± 1.1/hpf). Conclusions: It remains to be seen whether LE represents a novel pathological phenotype or is a variation of known chronic conditions. However, providers should consider in the evaluation of patients presenting with chronic dysphagia. Funding Agencies: None